2012
DOI: 10.1093/cid/cis660
|View full text |Cite
|
Sign up to set email alerts
|

Candida Osteomyelitis: Analysis of 207 Pediatric and Adult Cases (1970-2011)

Abstract: Candida osteomyelitis is being reported with increasing frequency. Localizing symptoms are usually present. Vertebrae are the most common sites in adults vs femora in children. Timely diagnosis of Candida osteomyelitis with extended courses of 6-12 months of antifungal therapy, and surgical intervention, when indicated, may improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
158
2
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 123 publications
(18 reference statements)
8
158
2
18
Order By: Relevance
“…Secondary destruction of articular cartilage and progressive bone deformity can occur; therefore, early detection and therapy are essential to prevent signifi cant morbidity. Because there are no specifi c clinical or radiologic fi ndings of Candida arthritis, only an appropriate culture permits diagnosis (7) (8) . Because of the persistency of the arthritis, despite conventional medical and interventional treatment for infl ammatory arthritis, the synovial fl uid is examined closely and repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary destruction of articular cartilage and progressive bone deformity can occur; therefore, early detection and therapy are essential to prevent signifi cant morbidity. Because there are no specifi c clinical or radiologic fi ndings of Candida arthritis, only an appropriate culture permits diagnosis (7) (8) . Because of the persistency of the arthritis, despite conventional medical and interventional treatment for infl ammatory arthritis, the synovial fl uid is examined closely and repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…The most common abnormalities include bone destruction, soft tissue extension/ swelling, intervertebral space/joint space narrowing, and epidural abscesses. Hypointense MRI images on T1WI as well as hyperintense images on T2WI were noted [102]. Irregularities of subchondral bone have also been noted [103].…”
Section: Osteomyelitismentioning
confidence: 92%
“…Another study, by Lavery et al, showed that of over 151 patients with lower extremity infections, the ratio was nearly equal, at 52 % male [ 11 ]. However, fungal osteomyelitis has been reported to have a statistically signifi cant male dominance [ 12 ]. Gender should not be considered an independent risk factor and osteomyelitis can affect anyone.…”
Section: Risk Factors For Osteomyelitismentioning
confidence: 99%
“…Other medical conditions resulting in immunosuppression, organ transplants, or any condition that alters neutrophil defense, humoral immunity or cell-mediated immunity, can increase susceptibility to infection and increase the risk of undiagnosed osteomyelitis. Additionally, those with chronic immunosuppression are more likely to be diagnosed with fungal originated osteomyelitis [ 12 ]. Circulation disorders are another risk factor that may decrease host immune response and increase the potential of a deep infection.…”
Section: Risk Factors For Osteomyelitismentioning
confidence: 99%
See 1 more Smart Citation